Reconstructing skeletal homeostasis through allogeneic hematopoietic stem cell transplantation in myelofibrosis - Mathias Schäfersküpper; Alexander Simon; Timur A. Yorgan; Felix N. von Brackel; Maximilian M. Delsmann; Anke Baranowsky; Nico Gagelmann; Francis Ayuk; Thorsten Schinke; Michael Amling; Nicolaus Kröger; Tim Rolvien (Nature Communications)
Abstract Myeloproliferative neoplasm-associated myelofibrosis is a clonal stem cell process characterized by pronounced bone marrow fibrosis associated with extramedullary hematopoiesis and splenomegaly. Allogeneic hematopoietic stem cell transplantation (allo-HSCT) represents the only curative treatment leading to bone marrow fibrosis regression. Here we provide an in-depth skeletal characterization of myelofibrosis patients before and after allo-HSCT utilizing clinical high-resolution imaging, laboratory analyses, and bone biopsy studies. Despite unimpaired bone microarchitecture at peripheral skeletal sites, we observe a marked increase in bone mineral density at the lumbar spine and proximal femur, which is histologically related to severe bone marrow fibrosis and osteosclerosis, fully normalizing after allo-HSCT. Importantly, the regression of fibrosis is accompanied by vanishing osteosclerosis along with restored osteoclastic resorption activity and whole-body calcium homeostasis. Together, our results provide evidence for an extensive reconstruction of skeletal homeostasis by allo-HSCT in MF, leading to rapid resolution of osteosclerosis.